2020
DOI: 10.1021/acsanm.0c00749
|View full text |Cite
|
Sign up to set email alerts
|

CuO Nanoparticles/Ti3C2Tx MXene Hybrid Nanocomposites for Detection of Toluene Gas

Abstract: Toluene is one of the harmful volatile organic compounds (VOCs) for both human health and environments. Thus, to prevent the hazardous effect of toluene, fast detection at an early stage is needed. CuO shows the merit for a wide range responsivity to VOCs but suffers from small response value, slow response/recovery speeds, and low durability. Herein, we report a facile preparation of CuO/Ti 3 C 2 T x MXene hybrids via electrostatic self-assembly. The CuO nanoparticles (∼7 nm) were uniformly dispersed on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(72 citation statements)
references
References 67 publications
1
71
0
Order By: Relevance
“…The response of the W 18 O 49 /Ti 3 C 2 T x sensor with more than 2 wt % of MXene decayed due to the presence of −F functional groups that were not fully eliminated after the solvothermal process, indicating the deteriorating effect of the −F functional group on the gas-sensing performance of MXene-based sensors. Due to the nonpolar structure of C-containing gas molecules such as toluene, MXenes do not show a good response to them. ,, Hermawan et al described the fabrication of hybrid heterostructures of CuO nanoparticles/Ti 3 C 2 T x MXene via electrostatic self-assembly. It was reported that CuO nanoparticles have an average size of 7 nm and were uniformly distributed over the interlayers and surface of Ti 3 C 2 T x MXene (Figure c).…”
Section: Experimental Perspectivementioning
confidence: 99%
“…The response of the W 18 O 49 /Ti 3 C 2 T x sensor with more than 2 wt % of MXene decayed due to the presence of −F functional groups that were not fully eliminated after the solvothermal process, indicating the deteriorating effect of the −F functional group on the gas-sensing performance of MXene-based sensors. Due to the nonpolar structure of C-containing gas molecules such as toluene, MXenes do not show a good response to them. ,, Hermawan et al described the fabrication of hybrid heterostructures of CuO nanoparticles/Ti 3 C 2 T x MXene via electrostatic self-assembly. It was reported that CuO nanoparticles have an average size of 7 nm and were uniformly distributed over the interlayers and surface of Ti 3 C 2 T x MXene (Figure c).…”
Section: Experimental Perspectivementioning
confidence: 99%
“…f) gas sensing linear fitting of R −1 versus C −1 based on the Langmuir isotherm model; g) response/recovery times; h) selectivity of CuO/Ti 3 C 2 T x -30 wt% to 50 ppm of tested gas; and i) relationship of response value with specific surface area. Adapted with permission [143]. Copyright 2020, American Chemical Society.…”
mentioning
confidence: 99%
“…Similar to microstructure-based volatile hydrocarbon vapors quantification (example: Sn 2+ doped NiO microspheres in Xylene detection with sub-ppm LOD) [ [390][391][392][393][394][395][396][397]. Wherein, Ag/Bi 2 O 3 nanocomposite and Graphene/SnO 2 NPs nanocomposite were found to perform remarkably in terms of their operation temperature (at room temperature) [394,397].…”
Section: Volatile Hydrocarbons Detection By Distinct Nanostructuresmentioning
confidence: 83%
“…Similar to microstructure-based volatile hydrocarbon vapors quantification (example: Sn 2+ doped NiO microspheres in Xylene detection with sub-ppm LOD) [ 389 ], nanocomposites, such as Pd/PdO/S-SnO 2 nanocomposite film, rGO/Co 3 O 4 nanocomposite, WO 3 decorated TiO 2 NPs nanocomposite, BGQD/Ag–LaFeO 3 nanocomposite, Ag/Bi 2 O 3 nanocomposite, AgO loaded LaFeO 3 nanocomposite, CuO NPs-Ti 3 C 2 Tx MXene nanocomposite, and Graphene/SnO 2 NPs nanocomposite were effectively applied in the detection of hydrocarbons as detailed in Table 5 [ 390 , 391 , 392 , 393 , 394 , 395 , 396 , 397 ]. Wherein, Ag/Bi 2 O 3 nanocomposite and Graphene/SnO 2 NPs nanocomposite were found to perform remarkably in terms of their operation temperature (at room temperature) [ 394 , 397 ].…”
Section: Volatile Hydrocarbons Detection By Distinct Nanostructurementioning
confidence: 99%